China from the margins : new narratives of the past and present - Williams, Emily R.; Cesarino, Loredana (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book explores and brings to light untold stories from the margins of Chinese society. It investigates and reveals grassroots and popular cultural beliefs, amusing anecdotes, items of lore, and accounts of the strange and the unusual. It delves into questions of identity formation, considering gender, sexuality, class, generational divides, subcultures, national minorities and online communities. It examines heritage-making practices and the persistence of marginalized memories. Bringing together views from cultural studies, literature, gender studies, cultural heritage, sociology, history and more, the book argues that neither the margins nor the centre can be understood in isolation, and that by focusing on the margins, a fuller picture of Chinese society overall emerges, including new perspectives on spatial and social marginality, on hierarchies of marginality, and on neglected spaces, voices and identities"--
Keywords: Marginality, Social -- China; China -- Social conditions; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Research